1996
DOI: 10.1021/jp962161o
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Correlated Calculations of Electric Properties of Nucleic Acid Bases

Abstract: Full geometry optimizations have been performed at the MP2 level of theory using the 6-31G(d,p) basis set for the five common nucleic acid bases (uracil, thymine, cytosine, adenine, and guanine) and three related bases (fluorouracil, 5-methylcytosine, and hypoxanthine). Several electric properties were subsequently calculated using the optimized geometries and the larger polarized basis sets of Sadlej. Including electron correlation decreases the magnitude of the dipole moments by 10-15% for every base except … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 32 publications
(59 reference statements)
6
45
0
Order By: Relevance
“…From the fully optimized geometries for benzene and pyridine (at the B3LYP/DZP level) and for the nucleic acid bases and three related bases [17] (at the MP2/6-31G** level), using noncorrelated (HF) and correlated (B3LYP and BP86) methods and the hierarchical sequence of AXZP (X ϭ D, T, Q) basis sets generated by Jorge et al, [8,12] electric properties were calculated and compared with theoretical and experimental results reported in the literature. Table I shows the convergence of the calculated components of the dipole moments and polarizabilities with the basis set quality in benzene, pyridine, uracil, cytosine, thymine, guanine, adenine, fluorouracil, 5-methylcytosine, and hypoxanthine at the HF and DFT levels of theory.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From the fully optimized geometries for benzene and pyridine (at the B3LYP/DZP level) and for the nucleic acid bases and three related bases [17] (at the MP2/6-31G** level), using noncorrelated (HF) and correlated (B3LYP and BP86) methods and the hierarchical sequence of AXZP (X ϭ D, T, Q) basis sets generated by Jorge et al, [8,12] electric properties were calculated and compared with theoretical and experimental results reported in the literature. Table I shows the convergence of the calculated components of the dipole moments and polarizabilities with the basis set quality in benzene, pyridine, uracil, cytosine, thymine, guanine, adenine, fluorouracil, 5-methylcytosine, and hypoxanthine at the HF and DFT levels of theory.…”
Section: Resultsmentioning
confidence: 99%
“…This conclusion is important, since experiences in electric property calculations of small molecules [12, 28 -32] have shown that reliable indications of the convergence of the HF results to the respective HF limits are slower, i.e., it is necessary to use larger basis sets to obtain it. Thus, from here on, the ADZP results will be used to compare with a selection of theoretical [17] and experimental [4,[21][22][23] , ␣ , and ⌬␣ values reported in the literature. For adenine, guanine, and hypoxanthine (two ring compounds), electrical property calculations using the AQZP basis set were not carried out (cf., Table I) because the computational time spent in these cases increase significantly.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations